Transformasi Digital Melalui Penerapan Aplikasi Digital Menu dalam Mendukung Kinerja UMKM di SWK Semolowaru - Gyska Indah Harya; Dian Nuningrum Adelia; Dinta Fernanda Maulidya; Firman Rizky Ramadhan; Jeniper Indah Pandiangan (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2024)
Micro, Small, and Medium Enterprises play a vital role in the Indonesian economy, but often face challenges in adopting digital technology. This community service aims to analyze the impact of implementing a digital menu as a tool for empowering Micro, Small, and Medium Enterprises, especially in the culinary sector. Digital menus are identified as innovations that not only facilitate business management but also improve customer experience through faster and more accurate access to information. This study uses a qualitative approach with an interview method on several Micro, Small, and Medium Enterprises in SWK Semolowaru, Surabaya. The results of community service that have been carried out are known that the use of digital menus significantly increases operational efficiency, reduces printing costs, and expands market reach through integration with digital platforms. the main challenges faced are limited human resources in mastering technology and the need for ongoing training. Therefore, support from the local government and related parties is needed to provide comprehensive training programs to improve the digital competence of Micro, Small, and Medium Enterprises. Empowering Micro, Small, and Medium Enterprises through digital menus has great potential to increase competitiveness in the digital era, thereby encouraging inclusive economic growth.